Violence and desire described by committed football-supporters in substance abuse treatment. Clinical psychodynamic findings - Elisabeth H Punzi (Mediterranean Journal of Clinical Psychology, 2020)
This study concerns male clients in substance abuse treatment, who were or had been football supporters, engaged in violence. Previous research has acknowledged the connection between football and violence, substances, homosociality and masculinity. Desire and treatment needs have however not been investigated. This study contributes to this knowledge gap. It is written from a treatment viewpoint, acknowledging current psychodynamic/analytical perspectives on gender, relationships, and affects. The study is based on the author’s clinical encounters with supporters who were in psychodynamic treatment due to problems with substance use. A thematic analysis of the author’s memories of the clinical encounters was performed. Three themes were identified; Alcohol and drugs, Desire and Clinical interaction. The results show that consumption of alcohol and cocaine was intermingled with the homosocial supporter-culture and accordingly with the clients’ social life, which needs to be acknowledged in treatment. Moreover, violence was not only connected to homosocial strivings and hypermasculine behaviors, but also to desire. Same-sex desire could for example arise during fighting, which could be an alluring part of violence, while simultaneously shame-provoking. The study shows that supporters, and possibly other homosocial groups, are more diverse than sometimes presented. Accordingly, clinicians who encounter committed football supporters should be open to questions of desire, including non-normative sexual experiences, while acknowledging that the topic might be difficult for clients. Clinicians also need to understand how intertwined supporter-culture and substances are, and discuss affects and relationships with clients.